Enhancing Supply Chain Resilience: Proactive Strategies for Disruptive Events - Hajarath, Krishna; Vummadi, Jayapal (International Journal of Supply Chain Management, 2024)
Purpose: This paper emphasizes the significance of proactive strategies in enhancing supply chain resilience against disruptions, focusing on natural disasters, geopolitical instability, and pandemics. Through risk assessment, scenario planning, and proactive measures like diversification, inventory optimization, and technology adoption, it proposes an integrated methodology for resilient supply chains. Methodology: Drawing from literature and real-world examples, this study develops a framework for supply chain resilience, emphasizing contingency planning and implementation techniques. Findings: The integrated methodology enhances companies' resilience and recovery capacity, mitigating the severity of disruption effects. Practical recommendations are offered for developing resilient supply chains in uncertain business environments. Unique Contribution to Theory, Practice and Policy: This study contributes by offering actionable recommendations, bridging theory and practice, to fortify supply chains against instability and uncertainty, thereby advancing both theoretical understanding and practical applications in supply chain resilience planning.